2023
DOI: 10.1038/s41467-022-35181-w
|View full text |Cite
|
Sign up to set email alerts
|

Finding shortest and nearly shortest path nodes in large substantially incomplete networks by hyperbolic mapping

Abstract: Dynamic processes on networks, be it information transfer in the Internet, contagious spreading in a social network, or neural signaling, take place along shortest or nearly shortest paths. Computing shortest paths is a straightforward task when the network of interest is fully known, and there are a plethora of computational algorithms for this purpose. Unfortunately, our maps of most large networks are substantially incomplete due to either the highly dynamic nature of networks, or high cost of network measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This algorithm can determine the angular coordinates of the hyperbolic embedding in H 2 and, more generally, extract other types of onedimensional embeddings. Hyperbolic latent space contains geometric information associated with the original network; in the context of H 2 , a recent study showed that shortest paths in the hyperbolic latent space are aligned along geodesic curves connecting endpoint nodes, and this alignment is sufficiently strong to allow the identification of shortest path nodes even in the case of substantially incomplete networks [179]. Finally, note that the hyperbolic embedding in the case of directed networks has been addressed in [180].…”
Section: Network Embedding In Hyperbolic and Lorentzian Spacesmentioning
confidence: 99%
“…This algorithm can determine the angular coordinates of the hyperbolic embedding in H 2 and, more generally, extract other types of onedimensional embeddings. Hyperbolic latent space contains geometric information associated with the original network; in the context of H 2 , a recent study showed that shortest paths in the hyperbolic latent space are aligned along geodesic curves connecting endpoint nodes, and this alignment is sufficiently strong to allow the identification of shortest path nodes even in the case of substantially incomplete networks [179]. Finally, note that the hyperbolic embedding in the case of directed networks has been addressed in [180].…”
Section: Network Embedding In Hyperbolic and Lorentzian Spacesmentioning
confidence: 99%